Longitudinal monitoring of ctDNA EGFR mutation burden from urine correlates with patient response to EGFR TKIs: A case series. (June 2017) - Tchekmedyian, Nishan; Mudad, Raja; Blanco, Fernando F.; Raymond, Victoria M.; Garst, Jordan; Erlander, Mark G.; Haura, Eric; Berz, David
Highlights: Patients with somatic EGFR mutations are eligible for tyrosine kinase inhibitors. Circulating tumor DNA (ctDNA) can be used to identify EGFR mutations. Quantitative ctDNA assessment has the potential to assess therapeutic response. Abstract: Targetable, somatic EGFR mutations are highly prevalent in patients with non-small cell lung cancer (NSCLC), making them eligible for tyrosine kinase inhibitor (TKI) therapy. Circulating tumor DNA (ctDNA), isolated from blood or urine, has been demonstrated to reliably identify somatic tumor associated EGFR mutations, specifically in patients with inconclusive biopsy. When conventional imaging modalities are inconclusive, quantitative assessment of systemic ctDNA burden has the potential to assess therapeutic response. We report on the clinical use of non-invasive, urinary ctDNA liquid biopsies for the ultrasensitive detection and longitudinal monitoring of ctDNA EGFR systemic mutation burden in five patients with NSCLC treated with EGFR TKIs. Urinary ctDNA-based quantitative assessment of systemic EGFR mutant allele burden is a non-invasive molecular diagnostic testing modality that has the potential to be utilized as an ancillary tool to assess disease burden and response to therapy.